Effects of a Tax‐Time Savings Intervention on Use of Alternative Financial Services among Lower‐Income Households. Issue 2 (21st December 2016) - Despard, Mathieu R.; Grinstein‐Weiss, Michal; Ren, Chunhui; Guo, Shenyang; Raghavan, Ramesh
Abstract : Alternative financial services (AFS) such as check cashing and payday loans may help unbanked households meet transaction and credit needs, yet often at a very high price. Saving tax refunds can help low‐ and moderate‐income (LMI) households build emergency savings as a way to reduce dependence on AFS and cope effectively with irregular cash flows and financial shocks. This study examined the impact on AFS use of message‐based interventions encouraging LMI households to save their refunds when they electronically filed their federal income tax returns. We found that 3 out of 18 interventions resulted in statistically significant reductions in credit‐related AFS use with small effect sizes. None of the interventions resulted in reduced transaction‐related AFS use. Other factors—especially prior AFS use and financial shocks—were strong predictors of AFS. Financially vulnerable households may need additional opportunities and protections to reduce dependence on AFS.